181k views
4 votes
Can someone plz give me the answer for this question?

Can someone plz give me the answer for this question?-example-1

1 Answer

2 votes

Answer:

see explanation

Explanation:

Given

f(x) =
e^(2x) - 4

let f(x) = y

y =
e^(2x) - 4

Switch x and y and solve for y, that is

x =
e^(2y) - 4 ( add 4 to both sides )

x + 4 =
e^(2y)

Take the ln of both sides

ln(x + 4) = ln
e^(2y) = 2y
ln_(e) = 2y

Divide both sides by 2

y =
(ln(x+4))/(2), that is


f^(-1) (x) =
(ln(x+4))/(2)

User Silmathoron
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.